2004
DOI: 10.1603/0022-2585-41.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and Mechanism of Resistance toBacillus sphaericusinCulex quinquefasciatus(Diptera: Culicidae) from China and Brazil

Abstract: Investigations on the inheritance and mechanism of resistance to Bacillus sphaericus Neide in Culex quinquefasciatus Say colonies, selected with strains C3-41 (RLCq1/C3-41) and 2362 (CqRL1/2362), were performed in China and Brazil, respectively. The progeny of reciprocal F1 crosses (susceptible female x resistant male and vice versa) from both resistant colonies responded alike in bioassays, indicating recessive inheritance. Data on larvae susceptibility from the backcross offspring between F1 and their respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…Diagnostic bioassays were performed to overcome this constraint, and, conversely, it not only discriminated susceptible and resistant larvae but also demonstrated that frequency of resistant individuals has not decreased along the generations analyzed, in despite of the introduction of susceptible individuals at 1:9 or 1:1 ratios in Rev2362 and RevIAB colonies, respectively. This bioassay was suitable for screening resistant individuals in samples, whose presence could not be directly detected by multiple concentrations assays and it is an important tool for monitoring B. sphaericus resistance since alleles already studied in this model showed to be recessively inherited Oliveira et al, 2004;Amorim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic bioassays were performed to overcome this constraint, and, conversely, it not only discriminated susceptible and resistant larvae but also demonstrated that frequency of resistant individuals has not decreased along the generations analyzed, in despite of the introduction of susceptible individuals at 1:9 or 1:1 ratios in Rev2362 and RevIAB colonies, respectively. This bioassay was suitable for screening resistant individuals in samples, whose presence could not be directly detected by multiple concentrations assays and it is an important tool for monitoring B. sphaericus resistance since alleles already studied in this model showed to be recessively inherited Oliveira et al, 2004;Amorim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Availability of Cqm1 receptors on the midgut is crucial for larvicidal action of Bin toxin and its alteration, or absence, can lead to high levels of B. sphaericus resistance (Nielsen-Leroux et al, 1995;Darboux et al, 2002;Oliveira et al, 2004;Romão et al, 2006). Four alleles of the receptor gene were found to display mutations which prevent the production of functional membranebound proteins and, therefore, binding of Bin toxin to midgut epithelium (Darboux et al, 2002(Darboux et al, , 2007Romão et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Each allele displays distinct resistance-associated mutations which result in potential transcripts for truncated soluble proteins lacking the GPI anchor (cpm1 GEO , cqm1 REC , cpm1 BP ) or for truncated GPI-anchored proteins which are still unable to bind Bin toxin due to the loss of 66 amino acids (cpm1 BP -del). The CqRL1/2362 colony, derived from eggs collected in the Recife Metropolitan Area (RMA; Brazil) and laboratory selected, displays high levels of resistance (resistance ratio [RR], Ͼ100,000) due to the failure of Bin toxin binding to microvillus receptors, and larvae from this colony were found to be homozygous for the cqm1 REC allele (26,27). Characterization of this allele showed a 19-nucleotide (nt) deletion which changes the frame of the protein coding sequence and originates a premature stop codon.…”
mentioning
confidence: 99%
“…The cpm1 GEO allele, detected in a C. pipiens laboratory-selected colony (GEO) from California, contains a nonsense mutation leading to the synthesis of a truncated protein lacking the glycosylphosphatidylinositol anchor and is therefore not able to localize to the apical membrane of the midgut epithelium (11,38). A 19-nucleotide deletion in the gene cqm1, here named cqm1 REC , was associated with the resistance of a C. quinquefasciatus laboratory colony (CqRL1/ 2362) originating from the city of Recife (Brazil), and this mutation prevents the expression of Cqm1 on the midgut brush border membranes (28,29,30). Two alleles were found in the C. pipiens BP population from France (8).…”
mentioning
confidence: 99%